The Effect of the Comparison of Zeolite and Limestone on the Degree of Acidity (pH) of Acid Mine Drainage (Case Study: PT. XYZ) - Karim Kasmudin; Fitria Fitria (Yayasan Pendidikan Insan Mulia Utan Sumbawa, 2026)
Acid Mine Drainage (AMD) is a serious environmental problem in the particularly Minerals mining industry, characterized by low pH and high concentrations of dissolved heavy metals. This study aims to analyze the effect of the mass ratio between natural zeolite and limestone as a neutralization medium and adsorbent in the AMD processing of PT. XYZ. The research method used was a batch experiment in the laboratory with five variations of the mass ratio of zeolite and limestone (100:0, 75:25, 50:50, 25:75, and 0:100) with a total mass of 10 grams per 500 mL of AMD sample. The parameter measured was the change in pH during a contact time of 90 minutes. The results showed that all variations were able to increase the AMD pH from an initial value of 2.6. The ratio of 25:75 (zeolite:limestone) showed the most optimal effectiveness, able to increase the pH to 8.02 in 60 minutes and remained stable to time 90 minutes. Limestone plays a dominant role in acid neutralization, while the presence of zeolite is thought to prevent the effects of zeolite on acid neutralization armouring (coating) on limestone particles and also absorbs existing metal ions. This combination proved more effective than using each ingredient alone. It was concluded that a mass ratio of 25:75 was the optimal ratio for AMD treatment in this case study.